Decision making in orthodontics extraction versus expansion - Tan-Zafra, Josievitz U.
The choice between the two extremes of tooth extraction versus dental arch expansion therapies has always been a source of debate in orthodontic treatment planning going all the way back to Edward Angle and Charles Tweed. This paper provides a systematic review of literature on the indications for extractions and expansion in orthodontic treatment and the advantages and disadvantages of each.
Keywords: Extraction; Expansion; Non-extraction.